2003
DOI: 10.1152/ajplung.00351.2002
|View full text |Cite
|
Sign up to set email alerts
|

CFTR activation in human bronchial epithelial cells by novel benzoflavone and benzimidazolone compounds

Abstract: Activators of the CFTR Cl- channel may be useful for therapy of cystic fibrosis. Short-circuit current ( Isc) measurements were done on human bronchial epithelial cells to characterize the best flavone and benzimidazolone CFTR activators identified by lead-based combinatorial synthesis and high-throughput screening. The 7,8-benzoflavone UCcf-029 was a potent activator of Cl- transport, with activating potency (<1 μM) being much better than other flavones, such as apigenin. The benzimidazolone UCcf-853 gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…Interestingly, the level of SCN Ϫ transport reached in the presence of the blocker was lower than that measured in resting conditions, before addition of forskolin. This may be explained by the fact that a fraction of CFTR is active in nonstimulated epithelia, as we have already reported in a previous study (33). The involvement of CFTR was further confirmed by carrying out similar experiments in CF epithelia (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Interestingly, the level of SCN Ϫ transport reached in the presence of the blocker was lower than that measured in resting conditions, before addition of forskolin. This may be explained by the fact that a fraction of CFTR is active in nonstimulated epithelia, as we have already reported in a previous study (33). The involvement of CFTR was further confirmed by carrying out similar experiments in CF epithelia (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Forskolin (20 M) treatments were for 5 min and H89 (10 M) pretreatment for 20 min. Potentiator treatments were at the previously published EC 50 (VRT-532, 5 M; UC CF-152, 50 M; PG-01, 300 nM; SF-03, 30 nM; UCCF-853, 3 M; ⌬F508 act-02, 70 nM; genistein, 30 M; UCCF-029, 2 M; UCCF-180, 10 M) (7,26,32,37,41,51), except where otherwise specified. After drug treatment, cells were lysed in buffer (1% NP-40, 50 mM Tris·HCl, pH 7.5, 200 mM NaCl, 5 mM MgCl 2, 15% glycerol) with protease (Complete mini protease cocktail, Roche Diagnostics) and phosphatase inhibitors [Na 3VO4 (0.2 mM), NaF (10 mM), MoO4 (1 mM), and ␤-glycerophosphate (50 mM)].…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have revealed multiple chemical classes of CFTR activators that likely function by direct interaction with CFTR, including flavones/isoflavones, benzo [c]quinoliziniums, xanthines, benzimidazolones, fluorescein derivatives, and benzoflavones (Illek et al, 2000;Galietta et al, 2001;Ma et al, 2002b;Caci et al, 2003;Springsteel et al, 2003). Various ΔF508-CFTR "potentiators" have been identified, including VX-770, phenylglycines, sulfonamides, and tetrahydrobenzothiophenes Pedemonte et al, 2005;Van Goor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%